Pengaruh Implementasi Content Management System Terhadap Kecepatan Kinerja Menggunakan One Way Anova - Retno Palupi; Andrew Eka Prasetya (Teknik Informatika, 2022)
This study analyzes the performance speed measures of the Content Management System (CMS), namely Concrete, Drupal, Joomla and Wordpress. The purpose of this study was to determine whether there is a difference or not in the implementation of the four CMS. The data used are categorical and numeric types, categorical data is the CMS type and numerical data is obtained from observations made by recording the CMS installation on an offline server using the Active Presenter application, then calculating the installation time, admin system and database migration. The data obtained are then processed using the One Way ANOVA method in Statistical Product and Services Solution (SPSS) version 23. The indicator used for data sampling is the performance speed of the CMS which is measured in seconds. From data processing and analysis using One Way Anova, it can be concluded that from the CMS used (Concrete, Drupal, Joomla and Wordpress) there is no significant difference to the speed of CMS performance. Each CMS has advantages, but in terms of speed of performance there is no significant difference.